EEG recording during an emotional face-matching task in children of mothers with interpersonal violence-related posttraumatic stress disorder. (30th January 2019) - Perizzolo, Virginie C.; Berchio, Cristina; Moser, Dominik A.; Gomez, Cristina Puro; Vital, Marylène; Arnautovic, Emina; Torrisi, Raffaella; Serpa, Sandra Rusconi; Michel, Christoph M.; Schechter, Daniel S.
Highlights: IPV-PTSD mothers and their children showed attentional bias to negative emotions. Maternal IPV-PTSD modulates child neural emotional processing. Child dlPFC hypoactivity (N170) upon negative-emotion stimuli. Children of IPV-PTSD mothers show enhanced sensitivity to negative emotions. Abstract: The aim of this study was to examine the effects of maternal interpersonal violence-related posttraumatic disorder (IPV-PTSD) on child appraisal of emotion, as measured by high-density electroencephalography (HD-EEG) during an Emotional Face-matching Task (EFMT). We recorded HD-EEG in 47 children of mothers with and without IPV-PTSD during an Emotional Face-matching Task (EFMT). Mothers and children each performed the EFMT. Behavioral results demonstrated that both mothers who were directly exposed to violent events, and their children, presented attentional bias toward negative emotions when processing facial stimuli. EEG findings confirmed differences in emotion appraisal between children of IPV-PTSD mothers and non-PTSD controls at scalp-level and in terms of source localization upon which children of IPV-PTSD mothers demonstrated decreased activation of the right dorsolateral prefrontal cortex (dlPFC) in response to angry and fearful faces as compared to non-PTSD children with respect to the N170 component. Our study, to our knowledge, is the first to show that maternal IPV-PTSD significantly affects a mother's own and her child's neural activity in response to facial expressions of negative emotion. These findings are potentially important to the development and study of effective interventions to interrupt intergenerational cycles of violence and trauma.